2017
DOI: 10.1056/nejmoa1613502
|View full text |Cite
|
Sign up to set email alerts
|

Association of Changes in Diet Quality with Total and Cause-Specific Mortality

Abstract: BACKGROUND Few studies have evaluated the relationship between changes in diet quality over time and the risk of death. METHODS We used Cox proportional-hazards models to calculate adjusted hazard ratios for total and cause-specific mortality among 47,994 women in the Nurses’ Health Study and 25,745 men in the Health Professionals Follow-up Study from 1998 through 2010. Changes in diet quality over the preceding 12 years (1986–1998) were assessed with the use of the Alternate Healthy Eating Index–2010 score,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
296
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 391 publications
(316 citation statements)
references
References 34 publications
(50 reference statements)
14
296
0
6
Order By: Relevance
“…A recent meta‐analyses showed that higher diet quality scores measured with the Alternate HEI, Alternate Mediterranean Diet, DASH score and the HEI‐2010 were associated with an estimated 17%‐26% reduction in risk of all‐cause mortality . A large study by Sotos‐Prieto et al found consistent associations between improved diet quality over 12 years as assessed by the Alternate HEI, Alternate Mediterranean Diet, and DASH scores and a reduced risk of death in the subsequent 12 years . While prior studies have assessed diet quality and mortality, we are the first to do so in the context of NAFLD.…”
Section: Discussionmentioning
confidence: 86%
“…A recent meta‐analyses showed that higher diet quality scores measured with the Alternate HEI, Alternate Mediterranean Diet, DASH score and the HEI‐2010 were associated with an estimated 17%‐26% reduction in risk of all‐cause mortality . A large study by Sotos‐Prieto et al found consistent associations between improved diet quality over 12 years as assessed by the Alternate HEI, Alternate Mediterranean Diet, and DASH scores and a reduced risk of death in the subsequent 12 years . While prior studies have assessed diet quality and mortality, we are the first to do so in the context of NAFLD.…”
Section: Discussionmentioning
confidence: 86%
“…Children, and their participating parent, work to increase fruits and vegetables per day and to decrease high-fat foods to lose weight and promote long-term health [60]. An emphasis is placed on developing sustainable healthy eating habits and these changes are shaped over time, a process of reinforcing successive approximations of a target behavior that helps to slowly and steadily build new habits [61].…”
Section: Fbt Treatment Componentsmentioning
confidence: 99%
“…In fact, previous research has shown that the health benefits of doing high and very high levels of PA remain for some time ; moreover, PA is an important determinant of cardiorespiratory fitness, which is a more stable biological marker with a strong inverse relationship with obesity and critical component for predicting major clinical outcomes in obesity . Future research with a longer follow‐up may shed more light on this issue; for instance, one study on the timing of dietary changes on subsequent health outcomes indicates that the associations were strengthened when changes over a longer duration were evaluated .…”
Section: Discussionmentioning
confidence: 99%